Indigenous Knowledge About Disaster in Folk Prose Narratives of Indonesian Coast - Rizki Nurislaminingsih; Yety Rochwulaningsih (Diponegoro University, 2022)
Indonesian people consists of various ethnic groups living in urban, rural, mountainous, and coastal areas. The people who inhabit each region have stories that describe the topography of the region and its culture. An example is people from coastal areas. The location of their residences which are close to the ocean makes them experts in recognizing natural signs and disaster characteristics from the sea. Their knowledge is shared with the social environment by verbal. One type of oral tradition originating from the natives is folk prose narratives such as legends, fairy tales, and stories of the origin of a place. This study aims to explore indigenous knowledge in folk prose narratives from the Indonesian coast. The results showed that the knowledge contained in folk prose narratives was how to recognize disaster signs from the sky (roaring wind, lightning flashes, pitch-dark sky, black cloud, and very heavy rain), disaster signs from the sea (low tides, hurricanes), ways to save yourself (climbing trees, climbing hills, and going to higher ground), and disaster prevention (not killing animals and cutting down trees carelessly). The conclusion is indigenous knowledge about disasters in folk prose narratives from the Indonesian coast is how to recognize natural signs, how to save themselves, and mitigation. The findings in this study are that Indonesian ancestors had knowledge in making flying vehicle and making fish feed on natural ingredient (chicken feathers).